2011
DOI: 10.1073/pnas.1101920108
|View full text |Cite
|
Sign up to set email alerts
|

Disentangling pleasure from incentive salience and learning signals in brain reward circuitry

Abstract: Multiple signals for reward-hedonic impact, motivation, and learned associative prediction-are funneled through brain mesocorticolimbic circuits involving the nucleus accumbens and ventral pallidum. Here, we show how the hedonic "liking" and motivation "wanting" signals for a sweet reward are distinctly modulated and tracked in this circuit separately from signals for Pavlovian predictions (learning). Animals first learned to associate a fixed sequence of Pavlovian cues with sucrose reward. Subsequent intraacc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

16
338
1
5

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 349 publications
(360 citation statements)
references
References 96 publications
16
338
1
5
Order By: Relevance
“…Our experiments do not settle how this coordination is accomplished or whether it is accomplished exclusively online. Still, our anatomical evidence from using the viral vector to trace the connections from the IL-injection sites confirmed that this region did not have detectable direct connections with the sensorimotor striatum but, rather, with regions (10) that should give the IL cortex direct access to circuits involved in flexibility and reinforcement as well as addiction (e.g., via projections to prelimbic neocortex and to the medial and ventral striatum) (3,4,6,7,15,23,25,26), and also to habit-promoting circuits through the central amygdala (27). Each could be important for the IL habit-toggling function.…”
Section: Control Groupmentioning
confidence: 80%
See 1 more Smart Citation
“…Our experiments do not settle how this coordination is accomplished or whether it is accomplished exclusively online. Still, our anatomical evidence from using the viral vector to trace the connections from the IL-injection sites confirmed that this region did not have detectable direct connections with the sensorimotor striatum but, rather, with regions (10) that should give the IL cortex direct access to circuits involved in flexibility and reinforcement as well as addiction (e.g., via projections to prelimbic neocortex and to the medial and ventral striatum) (3,4,6,7,15,23,25,26), and also to habit-promoting circuits through the central amygdala (27). Each could be important for the IL habit-toggling function.…”
Section: Control Groupmentioning
confidence: 80%
“…There is usually a close coupling of reward-proximal stimuli and actions to current value (7,21,24,25); the fact that the rats drank the devalued reward after this late manipulation of IL suggests that the reward might no longer have been aversive. However, this interpretation must face three issues.…”
Section: Control Groupmentioning
confidence: 99%
“…Such findings demonstrate that NAcc DA regulates the motivation for ("wanting") sweet-tasting stimuli (Nunes et al, 2013). In contrast, NAcc DA does not regulate appetite for homeostatic dietary need (Cousins and Salamone, 1994) or hedonic responding to ("liking") sweet stimuli (Smith et al, 2011). There is also interest in DA regulation of the motivation required under cognitively effortful conditions.…”
Section: Introductionmentioning
confidence: 96%
“…Conversely, in caudal shell, agonist microinjections reveal a 'hedonic coldspot', where opioid stimulation suppresses sucrose hedonic impact (Castro and Berridge, 2014;Pecina and Berridge, 2005). By contrast to the localized hotspot for sweetness 'liking', mu-opioid stimulations increase motivation to eat much more widely and homogeneously throughout the entire NAc shell (and in related structures), measured as increases in cue-triggered 'wanting' to obtain food rewards (eg, in instrumental breakpoint and pavlovian-instrumental transfer tests), as well as in food consumption (Castro and Berridge, 2014;Covelo et al, 2014;Maldonado-Irizarry et al, 1995;Pecina and Berridge, 2005;Pecina and Berridge, 2013;Smith and Berridge, 2005;Smith et al, 2011;Zhang and Kelley, 2000).…”
Section: Introductionmentioning
confidence: 99%